Low temperature preparation of oxygen-deficient tin dioxide nanocrystals and a role of oxygen vacancy in photocatalytic activity improvement - Supanan Anuchai (2018)
© 2017 Elsevier Inc. The introduction of oxygen vacancies (Vos) into tin dioxide crystal structure has been found as an effective method to improve its photocatalytic performance. Herein, oxygen-deficient tin dioxide (SnO2−x) nanocrystals were successfully prepared via a facile, one-step hydrothermal method at the temperature lower than those reported previously. The effect of hydrothermal temperature on phase composition and Voscontent was also firstly investigated. Due to its high oxygen vacancy concentration, the SnO2−xprepared at 80 °C provides the best photocatalytic degradation of methyl orange under UV–visible light. Scavenger trapping and nitroblue tetrazolium experiments also show that the Vosact as electron trapped sites and molecular oxygen adsorption sites, therefore increasing the production of active[rad]O2−radical which is the main species governing the photocatalytic activity of SnO2−xnanocrystals. Raman spectroscopy, X-ray photoelectron spectroscopy, photoluminescence measurement and electron spin resonance investigation clearly indicate that increasing the hydrothermal temperature results in the coexistence of SnO2−xand Sn3O4phases and the reduction of Vosconcentration which are detrimental to the photocatalytic performance. Density functional theory calculations also reveal that the presence of Vosis responsible for the upshift of valence band maximum and an extended conduction band minimum, hence a valence band width broadening and band gap narrowing which consequently enhance the photocatalytic performance of the oxygen-deficient SnO2−x.